The religious realization of the world of the Ancient inhabitants in Mesopotamia - الطلبي جمعة; معضد علي هاشم (Al-Adab Journal, 2019)
The religious belief of the Ancient inhabitants in Mesopotamia has been a fundamental focus of understanding and understanding their minds and their ways of thinking of the articular interlock that they evaluate or imagine of the underworld and so the upper world and the influence of the gods in its formulation and management ,so their life turn into short journey. In the course of this short life, the Ancient inhabitants in Mesopotamia must submit to the series intricacy from rituals and rites, which were gathered by time, and it is associated with the underworld and upper worlds, because the splitter between them formed the actual range for these traditions ,which dominated to thinking the Ancient inhabitants in Mesopotamia, so employs for it all efforts; mental and spiritual, and then begin applied this on the different aspects of life; literature and art and others. The art in different societies is a mirror of all community activity, and a record of awareness the people, who follow it. There are many evidences that art grows with religion and developed in the temples. In ancient Mesopotamia, art has reflected, throughout the ages, people’s awareness and realization of the universe and the world , it was not separated from religion, but was closely related to it, so maybe say, the arts were generally take of worship.